The role of leadership style and organisational structure in organisational effectiveness: a case study - Messaris, Annette (Rhodes University, Faculty of Commerce, Department of Management, 2015)
This research explores the role leadership style and organisational structure play in organisational effectiveness. Organisational effectiveness is one of the more complex terms to define although essential to understand in order for an organisation to grow and develop. A small to medium wine sales and distribution organisation, its leadership style and organisational structure were chosen as a focus of this case study. Organisational effectiveness in this study is understood by the terms growth and development using the Greiner Theory of Evolution and Revolution (1983). The literature explores the role of leadership style in organisational effectiveness by exploring various theories and focusing on The Full Range Leadership Model by Bass and Avolio (1994). In order to analyse the role of organisational structure in organisational effectiveness, the different forms of organisational structure and the role they have on the organisation's ability to grow and develop are explored. The primary purpose of this study is to investigate the role leadership style and organisational structure play in organisational effectiveness. A qualitative content analysis paradigm was used with a Case Study method. The data was gathered using structured interviews conducted on all 39 permanent staff members, day to day observation and the Multifactor Leadership Questionnaire (MLQ). The MLQ is used as a supporting tool to verify the leadership findings in the interviews. The data was analysed using NVivo10 and STATISTICA to gain insight into the leadership style and organisational structure of the organisation. The findings reflected that certain themes were repeatedly mentioned in the interviews and the definition of organisational effectiveness: structured leadership, more active leadership, lack of communication, staff motivation, staff training and development and organisational culture. As regards organisational structure, the following themes arose: The need for regular meetings, increased team work and more structured job descriptions. Through the analysis of all the components, leadership style and organisational structure were identified as having a significant role in organisational effectiveness which will be further analysed in this study.
Keywords: Uncatalogued